Estudo das transformações microestruturais decorrentes do tratamento criogênico em ligas de titânio (TiNbSn) pré deformadas a frio - Silva, Abraão Santos (2017)
Titanium alloys have been interesting combinations of mechanical properties and corrosion, thus generating great acceptance as structural material in aircraft components and also as a substitute of bone tissue, which justifies how many researches are being developed. The concentrations of the mechanical conformation (80% cold deformation), thermal treatments of solubilization, water quenching, Cryogenic treatment (-198ºC) and aging treatment through Vickers microhardness, metallography and image analysis techniques. The results demonstrate that the treatment is critical after an increase in the hardness of the alloy with less than 5.0% of tin, and this result is the result of Beta (CCC) and α "(Ortorrômbica) tension. Results from the hardness analyzes showed that the treatment should be followed by an increase in the number of martensite needles or an improvement in the hardness property. The image analysis demonstrated the same pattern in a quantitative manner. Construction of a temperature measurement system for the construction of a temperature measurement system.